Clinical Gastroenterological Manifestations as Criteria for the Pathology and Effectiveness of Surgical Correction of Reflux Disease of the Digestive System - Martynov Vladimir Leonidovich (Journal of Human and Animal Intestines, 2021)
The presence of numerous complaints of a gastroenterocolitic nature in patients with proven NBZ and CNDP and a sharp regression of these complaints after surgical correction of NBZ and CNDP allows us to conclude that the causes of these pathological manifestations are the failure of the Bauhinia valve and chronic violation of the duodenal patency, and the most adequate surgical aid for elimination of clinical manifestations of reflux disease is bauginoplasty with simultaneous duodenojejunostomy.
Keywords: Reflux Disease